Pengaruh Bentuk Jam’ul Qillah dan Jam’ul Katsrah Terhadap Pemahaman Ulama Terhadap Teks Al-Qur’an (Studi Komparatif Tafsir Al-Thabari dan Al-Mishbah) - Elsa Puspita (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the influence of plural forms in Arabic, especially jam’ul qillah and jam’ul katsrah, on the understanding of the mufassir in interpreting the verses of the Qur'an. The focus of this study is directed at the comparison between Tafsir al-Thabari which represents the classical approach, and Tafsir al-Mishbah which uses a contemporary approach. The difference in understanding of plural forms is believed to not only have an impact on linguistic interpretation, but also have consequences for the understanding of law and social values ​​in the Qur'an. This study uses a qualitative method with a content analysis approach to the tafsir texts containing plural forms. Data were collected through literature studies by examining primary and secondary sources, then analyzed descriptively-comparatively. The findings show that the forms jam’ul qillah and jam’ul katsrah can affect the breadth of meaning, both in legal and social verses. Through the comparison of the two tafsirs, it is seen that the linguistic aspect has an important role in forming the interpretative framework of the mufassir. These results are expected to enrich the linguistic study of the Qur'an and contribute to the methodology of interpretation based on language and context.